Effect of moderate and high intensity squats on countermovement jump performance across multiple sets of a contrast protocol - Bauer, P.; Sansone, P.; Mitter, B.; Seitz, L. B.; Tschan, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Post-activation potentiation (PAP) of countermovement jump (CMJ) performance following the completion of a conditioning activity (CA) is well-documented (Suchomel et al., 2015). However, the precise effect across multiple sets of paired exercises (CAs and CMJs) remains to be elucidated. The present study was designed to evaluate the PAP effects of moderate (MI) or high intensity (HI) squat exercises on CMJ performance across multiple sets compared to a control session with CMJs only (CTRL). Methods: Fifty-one resistancetrained male subjects (mean ± SD: age, 23.2 ±3.7 y; body mass, 87.4± 14.2 kg; squat 1RM, 158.1 ± 30.8 kg) participated in a randomized, cross-over study. After baseline assessment they performed a contrast PAP protocol comprising three sets of either MI (6×60% of 1RM) or HI squats (4x90% of 1RM) alternated with seven CMJs that were performed at 15 seconds, 1, 3, 5, 7, 9 and 11 minutes after the squats. A CTRL session was used where the sets of squats were replaced with one minute of recovery. Jump height recorded with a force plate during MI and HI was compared to that recorded during CTRL to calculate the PAP effect. A repeated measures ANOVA was used to assess the effects of condition (CTRL, MI and HI) and time and their interaction on JH. The alpha level of .05 was adjusted using the Bonferroni method for all ANOVA pairwise comparisons. Results: A significant interaction between conditions x time was found (F(18.01, 900.61)=3.99, p<.001). Further analysis indicated a significant decrease in JH at 15 seconds across all three sets of MI and HI compared to CTRL. Both squat protocols produced significantly higher JH at three minutes during the first set (+3.5 ± 8.8%and +3.1% ± 8.5%), whereas performance at five minutes was only increased in MI squats. No significant improvement was found in the second and third sets at any time point (p>.05). Discussion: Consistent with previous research, the present investigation demonstrates that CMJ performance was potentiated at three minutes during the first set of a contrast PAP protocol involving MI and HI squat exercises. Conversely, no PAP effect was observed in the second and third sets. These findings contrast with previous studies reporting an improvement in jump performance across three sets of squat contrast protocol (Baker, 2008). One possible explanation for the present findings is that fatigue may have accumulated in the second and third sets thus masking the PAP effect.